“RELIGION Á LA CARTE” AND FAMILY - Kratochvila, Michal (European Scientific Journal, ESJ, 2013)
To understand the spiritual behaviour of people is complicated because more similar terms describe this phenomenon, such as religiosity, spirituality, mysticism, paranormal and supernatural occurrence. The new phenomenon of contemporary religiosity is called spiritual nomadism or religious tourism or ‘religion á la carte’. The ‘religious market’ offers wide scale options: horoscope, palmist, amulets, seminars of magic, table-turning or fengshui. Our target is to explore the connection between the value of family of respondents and non-Christian nonaffiliated religiosity. This research demonstrates the characteristics and attitudes of the non-Christian nonaffiliated religiosity through horoscope, divination, magic, witchcraft, table-turning, superstition, east-philosophies and phenomenon of UFO. The analysis indicates the attitude of the respondents to the institution of marriage and to the next generation by children, by adults and by grandparents respondents. The consequences are based on the interview of 2020 respondents (representative by county, age, gender, education, number of habitants and nationality). In the research were used univariate, bivariate and multivariate analyses.